SPATIAL METAPHORS AS A MEANS OF PERSUASION IN ROMANS 5:12-21 - A. Potgieter (Acta Theologica)
George Lakoff and Mark Johnson’s seminal book Metaphors we live by (1980) makes us realise that a metaphor is not merely a linguistic phenomenon, but also a conceptual, socio-historical, neural, and bodily phenomenon establishing mental models. Romans 5:12-21 abounds with with rich imagery. The rhetorical impetus of pericope is often highlighted and the imagery of persuasion is often overlooked. The value that spatial metaphors, in particular, add to Paul’s argument also have a rhetorical function. This article investigates persuasion in Romans 5:12-21, drawing on spatial metaphors.